Induction of Autophagy by Pterostilbene Contributes to the Prevention of Renal Fibrosis via Attenuating NLRP3 Inflammasome Activation and Epithelial-Mesenchymal Transition - Wang, Ying-Jan; Chen, Yu-Ying; Hsiao, Ching-Mao; Pan, Min-Hsiung; Wang, Bour-Jr; Chen, Yu-Chi; Ho, Chi-Tang; Huang, Kuo-Ching; Chen, Rong-Jane (Frontiers in Cell and Developmental Biology, 2020)
Chronic kidney disease (CKD) is recognized as a global public health problem. NLRP3 inflammasome activation has been characterized to mediate diverse aspect mechanisms of CKD through regulation of proinflammatory cytokines, tubulointerstitial injury, glomerular diseases, renal inflammation and fibrosis pathways. Autophagy is a characterized negative regulation mechanism in the regulation of the NLRP3 inflammasome, which is now recognized as the key regulator in the pathogenesis of inflammation and fibrosis in CKD. Thus, autophagy is undoubtedly an attractive target for developing new renal protective treatments of kidney disease via its potential effects in regulation of inflammasome. However, there is no clinical useful agent targeting the autophagy pathway for patients with renal diseases. Pterostilbene (PT, trans-3,5-dimethoxy-4-hydroxystilbene) is a natural analogue of resveratrol that has various health benefits including autophagy inducing effects. Accordingly, we aim to investigate underlying mechanisms of preventive and therapeutic effects of PT by reducing NLRP3 inflammasome activation and fibrosis through autophagy-inducing effects. The renal protective effects of PT were evaluated by potassium oxonate (PO)-induced hyperuricemia and high adenine diet-induced CKD models. The autophagy induction mechanisms and anti-fibrosis effects of PT by down-regulation of NLRP3 inflammasome are investigated by using immortalized rat kidney proximal tubular epithelial NRK-52E cells. To determine the role of autophagy induction in the alleviating of NLRP3 inflammasome activation and EMT, NRK-52E with Atg5 knockdown (NRK-Atg5-(2)) cells were applied in the study. The results indicated that PT significantly reduces serum uric acid levels, liver xanthine oxidase activity, collagen accumulation, macrophage recruitment, and renal fibrosis in CKD models. At the molecular levels, pretreatment with PT downregulating TGF--triggered NLRP3 inflammasome activation and subsequent EMT in NRK-52E cells. After blockage of autophagy by treatment of Atg5 shRNA, PT loss of its ability to prevent NLRP3 inflammasome activation and EMT. Taken together, we suggested the renal protective effects of PT in urate nephropathy and proved that PT induces autophagy leading to restraining TGF-β-mediated NLRP3 inflammasome activation and EMT. This study is also the first one to provide a clinical potential application of PT for a better management of CKD through its autophagy inducing effects.